2020
DOI: 10.1101/2020.02.10.941435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intron retention as a new pre-symptomatic marker of aging and its recovery to the normal state by a traditional Japanese multi-herbal medicine

Abstract: Intron retention as a new marker of the pre-disease state and its recovery to the 1 normal state by a traditional Japanese multi-herbal medicine 2 3 Running title: Recovery of alternative splicing from the senescence to healthy type by 4 an herbal medicine 5 6 7

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Increase in transcriptional noise and production of isoforms with altered functionality [73,74] Disruption to RNA surveillance Failure of RNA quality control and fine tuning of gene expression [77,115] Altered dynamics of RNA turnover Enhanced stability of SASP mRNAs [81,82] Defective RNA export Altered subcellular localisation of mRNAs, nuclear accumulation and impaired translation of mRNAs [88,116] Compromised telomere maintenance…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in transcriptional noise and production of isoforms with altered functionality [73,74] Disruption to RNA surveillance Failure of RNA quality control and fine tuning of gene expression [77,115] Altered dynamics of RNA turnover Enhanced stability of SASP mRNAs [81,82] Defective RNA export Altered subcellular localisation of mRNAs, nuclear accumulation and impaired translation of mRNAs [88,116] Compromised telomere maintenance…”
Section: Mechanismmentioning
confidence: 99%
“…Recent evidence has also suggested that dynamic retained intron events occur in senescence and in aged tissues, and were negatively correlated with the expression of their host genes [73]. Accumulation of retained introns has also been described in the pre‐symptomatic stage of ageing in wild‐type mouse models [74]. Aberrant isoforms may have dominant negative properties, altered functional characteristics or misdirected subcellular localisation which may have profound implications for cells, tissues and systems and contribute to ageing and senescence phenotypes.…”
Section: Potential Mechanistic Links Between Disrupted Splicing Regul...mentioning
confidence: 99%
“…In addition, Green et al [41] reported a positive association between decreased IR in nuclear-detained mRNA and enhanced expression of regulators of immunocyte transcription and inflammatory response. IR was even proposed as a biomarker for aging and pre-obese state [42,43]. For a long time, 3' UTR introns are viewed as marks for nonfunctional transcripts resulting from genomic noise, mutation, and incorrect splicing [44][45][46].…”
Section: Intron Retentionmentioning
confidence: 99%